Resident and recruited macrophages differentially contribute to cardiac healing after myocardial ischemia - Weinberger, Tobias; Denise, Messerer; Joppich, Markus; Fischer, Maximilian; Garcia Rodriguez, Clarisabel; Kumaraswami, Konda; Wimmler, Vanessa; Ablinger, Sonja; Räuber, Saskia; Fang, Jiahui; Liu, Lulu; Liu, Wing Han; et al. (eLife, 2024)
Cardiac macrophages are heterogenous in phenotype and functions, which has been associated with differences in their ontogeny. Despite extensive research, our understanding of the precise role of different subsets of macrophages in ischemia/reperfusion (I/R) injury remains incomplete. We here investigated macrophage lineages and ablated tissue macrophages in homeostasis and after I/R injury in a CSF1R-dependent manner. Genomic deletion of a fms-intronic regulatory element (FIRE) in the Csf1r locus resulted in specific absence of resident homeostatic and antigen-presenting macrophages, without affecting the recruitment of monocyte-derived macrophages to the infarcted heart. Specific absence of homeostatic, monocyte-independent macrophages altered the immune cell crosstalk in response to injury and induced proinflammatory neutrophil polarization, resulting in impaired cardiac remodeling without influencing infarct size. In contrast, continuous CSF1R inhibition led to depletion of both resident and recruited macrophage populations. This augmented adverse remodeling after I/R and led to an increased infarct size and deterioration of cardiac function. In summary, resident macrophages orchestrate inflammatory responses improving cardiac remodeling, while recruited macrophages determine infarct size after I/R injury. These findings attribute distinct beneficial effects to different macrophage populations in the context of myocardial infarction.
Artikelversion: 29. Mai 2024
Gesehen am 28.11.2024